(untitled) (CIPEEX, 2025)
Inflammatory fibrous hyperplasia is a reactive oral lesion of the fibrous connective tissue, common in complete denture users and frequently observed in primary health care services. This case report describes the treatment of a patient with inflammatory fibrous hyperplasia, from surgery to rehabilitation, after referral from the Primary Health Care Unit to the School of Dentistry’s teaching clinic at Unievangélica. The patient, a 40-year-old female smoker, was diagnosed with hyperplasia located in the upper vestibular sulcus, presenting firm consistency, color similar to the adjacent mucosa, well-defined borders, and symptoms. The lesion was associated with prolonged use of an ill-fitting maxillary complete denture. After clinical evaluation and treatment planning, the lesion was removed with a high-power laser under local anesthesia, and the material was sent for histopathological analysis. Subsequently, the denture was relined with surgical cement and repositioned, allowing immediate rehabilitation. Thus, laser removal proved to be effective and minimally invasive, promoting good healing and postoperative comfort. Immediate rehabilitation contributed to both aesthetics and functionality during the tissue repair process. In conclusion, this case reinforces the importance of the Unified Health System (SUS) and the integration between primary health care and teaching clinics in providing specialized, accessible, and effective treatments. The patient remains under clinical follow-up to ensure prosthetic adaptation and treatment success.